Biofabrication of choroid-retina tissue construct for modelling of age-related macular degeneration disease - Tan, Edgar Yong Sheng (2019)
Age-Related Macular Degeneration (AMD) is a major cause of blindness affecting everyone above the age of fifty. The main pathological effect is the uncontrolled growth of blood vessel below the retina layer which results in neovascularisation and leaked fluid within the Bruch’s Membrane. Till date, there is no cure and limited treatment options to treat AMD. There is a need for a realistic and biomimetic choroid retina tissue model to enable in-depth investigation of the diseases and to enable speedy development of new treatment options. In this project, a choroid-retina tissue model was fabricated. The Choroid-Retina tissue is made of two distinct tissues layers consist of different types of cells with different requirements, properties and functions. The layer of retina cells should present hexagonal morphology on an ultrathin substrate; while the choroid layer must be in 3D, at high resolution and interconnected. In this project, 2 different biofabrication processes were used to develop the biomimetic Choroid-Retina Tissue Construct for Modelling of Age-Related Macular Degeneration Disease. The first step involves the development of an ultrathin and porous membrane to mimic the native Bruch’s Membrane for supporting a layer of functional retinal pigmented epithelium (RPE) cells. The membrane was produced through solution drop casting of a polycaprolactone/polyethylene glycol (PCL/PEG) solution. The RPE cells were cultured over a period of 15 days. The cells were able to form an epithelial barrier function on the 3rd day of culture similar to those grown on a PET (Polyethylene Terephthalate) membrane. The process is simple and can yield an ultra-thin, porous and free-standing membrane. This membrane was shown to be able to elicit RPE cell’s response and filtration properties that mimics a Bruch’s membrane. The second step involves the development of a 3D choroidal capillary vasculature via bioprinting. Bioprintable hydrogel materials were formulated and evaluated for optimal biocompatibility with endothelial (HUVECs) cells. An innovative printing strategy was optimised further so that the natural occurring hydrogel with extremely low viscosity such as collagen could be printed into a free-standing 3D construct. As a result, vasculature design feature with resolution of 100 µm was achieved for soft hydrogels such as Gelatin Methylacrylate (GelMA) and Collagen Type I. The novel printing approach relies on the use of surface interaction between the primary hydrogel (collagen or GelMA) and an bioinert secondary hydrogel, Pluronic, to create self-limiting swelling in order to achieve high resolution printing. A bioprinted 3D collagen construct of 1.5mm thickness, with pre-determined pore size of 400 µm and strut size of 100 µm, was seeded with HUVECs and cultured for 12 days. The experimental results indicated that the endothelial cells (HUVECs) was able to vascularise and was functional as demonstrated by the production of platelet endothelial cell adhesion molecule-1 biomarkers (CD31) and vWF (von Willebrand Factor). The 3D structure was produced to serve as a matrix for the formation of capillary structures. Lastly, the feasibility of creating a sandwich retinal-photoreceptor construct by combining the ultrathin membrane and bioprinted hydrogel was demonstrated. A hybrid 3D construct was created consisting of RPE cell-seeded ultrathin membrane and the photoceptor-like cells Y79. In summary, this work presents a novel hybrid approach with different biofabrication strategies. The resultant tissue construct could be used a possible tissue model to be employed in pharmaceutical companies for drug testing of AMD patients.